DESENTRALISASI DAN PENGELOLAAN WILAYAH PESISIR DI INDONESIA STUDI PADA DESA KOHOD KECAMATAN PAKUHAJI KABUPATEN TANGERANG - Endiarjati Dewandaru Sadono (Jurnal Kawistara, 2017)
The management of coastal areas in Indonesia has now been decentralized. This study tries to analyze qualitatively how the coastal area management has been done in Tangerang District, more precisely in Kohod Village, Pakuhaji Sub-District. Kohod Village became one of the three pilot projects village of Kampung Sejahtera conducted by Organisasi Aksi Solidaritas Era Kabinet Kerja (OASE Kabinet Kerja). Despite the considerable potential of coconut and laksa noodle development, but poverty, unemployment and slums are still the major problem in Kohod Village. Therefore, the development of coastal areas in this village can’t be left entirely to the local community. It takes the role of the government and private sector to support the development acceleration in this village. Thus, the development of coastal areas in Kohod Village should be done using collaborative approach.